2008
DOI: 10.1021/jp8018952
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer Probe Induced Formation of α-Cyclodextrin Nanotubular Suprastructures: A Concentration Dependent Process

Abstract: A suitably sized charge transfer probe of an elongated geometry can induce the formation of R-cyclodextrin nanotubular suprastructures, a rare event because of size restriction of the host. The specific molecular structure is found to be responsible only for the 1:2 guest-host complex formations. No evidence of the formation of the 1:1 complex is found. Steady-state fluorescence anisotropy and atomic force microscopy show that the nanocomposites club with other such species very efficiently to form nanotubes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 41 publications
(37 reference statements)
9
56
1
Order By: Relevance
“…The shapes roughly correspond to nanosheet structures after being fractured and replicated. This kind of nanosheet structure is apparently different from the nanotubes and their SA as reported before [23][24][25][26][27][28][29].…”
Section: Tem Characterizationcontrasting
confidence: 61%
See 2 more Smart Citations
“…The shapes roughly correspond to nanosheet structures after being fractured and replicated. This kind of nanosheet structure is apparently different from the nanotubes and their SA as reported before [23][24][25][26][27][28][29].…”
Section: Tem Characterizationcontrasting
confidence: 61%
“…Later similar SA structures of CD nanotubes have also been reported by some other research groups [26][27][28][29][30][31][32][33]. Jaffer et al and Sowmiya et al found that trans-2-[4-(dimethylamino)styryl]benzothiazole (DMASBT) could induce the formation of CD nanotubes and their rodlike SA [26][27][28], although they suggested that the SA consisted of nanotubes filled with DMASBT only and no empty CD was involved [28].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Fluorescence spectroscopy coupled with atomic force microscopy can serve as a very effective tool to understand this effect. The steady state and time-resolved fluorescence can tell us about the encapsulation of the guest molecules through a well-established procedure (see later), whereas steady state fluorescence anisotropy can let us know about the orientation and the ordered arrangement of the fluorophore, and the atomic force microscopy can give us a clearer view of the whole system so as to confirm our propositions [25][26][27]. The drug concentration has been proved to have profound effect on the nanotubular suprastructures formed by a-CD where the space constraint is a major factor [27].…”
Section: Introductionmentioning
confidence: 99%
“…[61] Purakayastha and co-workers confirmed CD-based host-guest complex formation by using AFM analysis techniques. [62,63] From the AFM topography of the surface morphology, Dionisio et al demonstrated that host-guest interactions occur among the polymer chains in the polymeric blending. [64] Liu and co-workers also reported the hierarchical structure of IMC-loaded poly(amidoamine) hydroxyl-terminated dendrimers and the nature of IMCdendrimer interactions by studying high-resolution STM micrograph images.…”
Section: Afm Analysismentioning
confidence: 99%